2012
DOI: 10.1007/s11940-012-0194-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative Disease and REM Behavior Disorder

Abstract: Patients with cerebral degenerative conditions commonly suffer from a variety of sleep disorders, including sleep-disordered breathing, insomnia, parasomnias (REM sleep behavior disorder), circadian rhythm disturbances, and restless legs syndrome. When these sleep disorders go unrecognized and untreated, they can lead to decreased quality of life and worsening neurological symptoms related to the underlying condition. Appropriate management initially requires taking a careful history from the patient and bed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Several among the available studies did not reveal any alteration in the endothelial function of migraineurs. Six of them did not find any difference in FMD between migraineurs and control subjects (Table  2) [20-23,25,26] and a further study confirmed the lack of any alteration in endothelial function assessed by PAT ratio (Table  3) [32]. Three studies assessing peripheral vasodilation after pharmacological stimuli found comparable responses in subjects with and without migraine (Table  3) [20,33,35].…”
Section: Reviewmentioning
confidence: 90%
See 3 more Smart Citations
“…Several among the available studies did not reveal any alteration in the endothelial function of migraineurs. Six of them did not find any difference in FMD between migraineurs and control subjects (Table  2) [20-23,25,26] and a further study confirmed the lack of any alteration in endothelial function assessed by PAT ratio (Table  3) [32]. Three studies assessing peripheral vasodilation after pharmacological stimuli found comparable responses in subjects with and without migraine (Table  3) [20,33,35].…”
Section: Reviewmentioning
confidence: 90%
“…Most of them assessed endothelial function by measuring FMD (Table  2) [20-30], some used PAT (Table  3) [31,32], some measured peripheral vasodilation in response to pharmacological stimuli (Table  3) [20,30,33-35], and others assessed endothelial progenitor cells (EPCs) (Table  4) [23,36,37]. Findings were not consistent across the studies.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Prescribe caffeinated drinks from the morning until early afternoon, but avoid caffeine if the patient has Periodic Leg Movement Disorder of Sleep, or Restless Leg Syndrome [103]. …”
Section: Treatmentmentioning
confidence: 99%